Synthesis of sugar esters in solvent mixtures by lipases from Thermomyces lanuginosus and Candida antarctica B, and their antimicrobial properties - Ferrer, Manuel; Soliveri, J.; Plou Gasca, Francisco José; López-Cortés, Nieves; Reyes-Duarte, Dolores; Christensen, Morten; Copa-Patiño, J.L.; Ballesteros Olmo, Antonio (Enzyme and Microbial Technology, 2005)
The lipases from Thermomyces lanuginosus (immobilized by granulation with silica) and Candida antarctica B (adsorbed on Lewatit, "Novozym 435") were comparatively assayed for the synthesis of sugar esters by transesterification of sugars with fatty acid vinyl esters in 2-methyl-2-butanol:dimethylsulfoxide mixtures. We found that lipase from C. antarctica B is particularly useful for the preparation of 6,6’-di-acylsucrose, whereas T. lanuginosus lipase catalyzes selectively the synthesis of 6-O-acylsucrose. The granulated T. lanuginosus lipase retained more than 80% of its initial activity after 20 cyles of 6 hours. Both lipases were similarly effective for the regioselective synthesis of 6’-O-palmitoylmaltose and 6-O-lauroylglucose. The effect of the synthesized sugar esters on the growth in liquid medium of various microorganisms (Gram-positive, Gram-negative and yeasts) was evaluated. 6-O-lauroylsucrose and 6’-O-lauroylmaltose inhibited the growth of Bacillus sp. at a concentration of 0.8 mg/ml, and of Lactobacillus plantarum at 4 mg/ml. Sucrose dilaurates and 6-O-lauroylglucose did not show antimicrobial activity, probably due to their low aqueous solubility. As regards the inhibition of yeasts, none of the tested carbohydrate esters inhibited significantly the growth of Zygosaccharomyces rouxii and Pichia jadinii. We thank Prof. Manuel Bernabé (Instituto de Química Orgánica, CSIC, Madrid, Spain) for help with NMR analysis. We thank Mr. Naoya Otomo (Mitsubishi-Kagaku Foods, Tokyo) for providing us a sample of sucroester L-1695. We are very grateful to Jordi Sucrana (SKW Biosystems, Barcelona, Spain) for technical help and fruitful suggestions. We thank CONACyT (Mexico) for a research fellowship to DRD. This work was supported by the European Union (Project BIO4-CT98-0363) and the Spanish CICYT (Project BIO2002-00337). Peer reviewed